Levels of pedagogical excellence in teaching of professions - Šernas, Vytautas (Acta Paedagogica Vilnensia, 1998)
Pedagogical excellence of vocational teacher is a complex of character features that help him to a) efficiently provide current knowledge of the profession, to form professional skills and abilities; b) help students to develop their natural talents, especially when they are relevant to the profession; c) to nurture favourable attitudes to the profession; d) to foster personal qualities and character traits required for the profession and life (diligence, sense of duty, honesty, sense of responsibility, a culture of cooperation it, etc.). The article describes and discusses five levels of professional excellence, from very low, when the teacher in the classroom only informs, showing no interest in whether the students understood, to very high, when the teacher already has his own style and system of educational activities, and educates not only professionals of own field, but also personalities.
Keywords: professional development; personal growth; educational qualifications; educational excellence